Meaning-Less Differences: Exposing Fallacies and Flaws in "The Word Gap" Hypothesis That Conceal a Dangerous "Language Trap" for Low-Income American Families and Their Children. Issue 1 (2nd January 2017) - Baugh, John
ABSTRACT: The present article compares and contrasts linguistic findings from longitudinal studies of low-income Americans derived from evidence of recorded family speech interactions. Hart and Risley (1995) employed research assistants who spent 1 hour per month observing language usage among families from different socioeconomic backgrounds in their homes for 2.5 years. Baugh (1983) spent 40 hours per week during seven consecutive summers between 1969 and 1976 as a participant observer in a low-income African American community, conducting tape recorded interviews with African American families in various social circumstances during the final 4 years, which always included recorded interviews within each family home. Comparison of the linguistic results derived from the alternative data collection procedures allow for a reinterpretation of Hart and Risley's (1995, 2003) conclusions, casting doubt on their findings as well as their speculations about future linguistic prospects for Americans from diverse racial and socioeconomic backgrounds due to false positive interpretations of their results that wrongly conclude deceptively enticing causalities. Regrettably, the alleged "word gap" is another incarnation of a deficit language hypothesis that is fundamentally flawed and woefully uninformed by decades of extensive linguistic research that has been conducted by many different linguists in various American inner-city communities since 1968.